TEACHER IMAGES IN “THE PROFESSOR” BY CHARLOTTE BRONTE (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores the representation of teacher figures in Charlotte Bronte’s The Professor (1857), focusing on how Bronte constructs the teacher’s role as both a moral and intellectual symbol. Through the analysis of William Crimsworth, Mademoiselle Reuter, and Frances Henri, the study reveals contrasting educational philosophies shaped by ethics, ambition, and sincerity. Bronte’s depiction of the teacher transcends professional identity, portraying education as a means of personal growth, moral discipline, and social transformation. The paper also examines how gender dynamics and Victorian educational ideals influence the portrayal of authority and emotional restraint within pedagogical relationships. The research concludes that Bronte envisions teaching as a spiritual vocation rooted in truth, empathy, and intellectual independence.